OPERATION ORGANIZING ALGORITHM OF DISTRIBUTED DSS UNDER HEAVY LOAD CONDITIONS - Гулак, Наталія; Дубчак, Олена (SWorldJournal, 2024)
Introduction. The decision support system (DSS) is an interactive automated system. It helps to use data and models to identify and solve problems, make decisions. The main task in decision making is to choose the best option to achieve a certain goal or